An empirical examination of barriers to acceptance of integrated paddy and beef cattle farming in Indonesia - Purnomo, Sutrisno Hadi; Sari, Ayu Intan; Emawati, Shanti; Rahayu, Endang Tri (Asian Journal of Agriculture and Rural Development, 2023)
This research aims to identify the barriers to the spread of integrated paddy and beef cattle farming and the influence of these barriers on Indonesian farmers’ acceptance of integrated farming. Quantitative methods were used to examine the barriers to integrated agriculture acceptance. A direct survey was conducted in which questionnaires were distributed to respondents. In addition, a research framework for the acceptance of integrated agriculture was developed using the technology acceptance model (TAM). Several data analysis methods were employed, including descriptive analysis, confirmatory factor analysis (CFA), and structural equation modelling (SEM). Data were obtained from 310 organic paddy farmers in Boyolali Regency, Central Java, Indonesia. The data were analysed using LISREL 8.8 software to assess the influence of barriers on the acceptance of integrated farming. SEM yielded the following results: x2 degree 1.77, GFI 0.92, AGFI 0.90, CFI 0.94, and RMSEA 0.06. As a result, we concluded that the goodness-of-fit index met the recommended criteria and that the model corresponded to the data provided, which allowed us to continue with the hypothesis testing. The results of hypothesis testing showed that the factors that significantly influenced the acceptance of integrated farming were barriers in the areas of production, knowledge, government, and economics. The practical implication of the research results is that by reducing barriers to production, knowledge, government, and economics, the acceptance of paddy and beef cattle integration can be increased.